2020
DOI: 10.7705/biomedica.5149
|View full text |Cite
|
Sign up to set email alerts
|

Salivary markers of oxidative stress and periodontal pathogens in patients with periodontitis from Santander, Colombia

Abstract: Introduction: Periodontitis affects more than 20% of the Latin American population.Oxidative markers are associated with greater progression of periodontitis; therefore, its role in pathogenesis should be studied.Objective: To determine the prevalence of the main oral bacteria and viruses associated with periodontitis and estimate the total antioxidant capacity and lipid peroxidation in saliva from patients with periodontitis.Materials and methods: We conducted systemically a cross-sectional study in 101 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…This disease impacts heavily on people’s quality of life, as it will inevitably lead to tooth loss if left untreated. The Gram-negative, nonmotile, facultative anaerobic bacterial pathogen Aggregatibacter actinomycetemcomitans is strongly associated with aggressive (grade C) periodontitis in young individuals and adolescents ( 1 3 ), and it is one of the most prevalent microorganisms in patients with periodontitis ( 4 ). Importantly, A. actinomycetemcomitans has been associated with serious nonoral infections, such as endocarditis and brain abscesses ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…This disease impacts heavily on people’s quality of life, as it will inevitably lead to tooth loss if left untreated. The Gram-negative, nonmotile, facultative anaerobic bacterial pathogen Aggregatibacter actinomycetemcomitans is strongly associated with aggressive (grade C) periodontitis in young individuals and adolescents ( 1 3 ), and it is one of the most prevalent microorganisms in patients with periodontitis ( 4 ). Importantly, A. actinomycetemcomitans has been associated with serious nonoral infections, such as endocarditis and brain abscesses ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been observed that Aggregatibacter actinomycetemcomitans, an oral pathogen, secretes a leukotoxin that can bind to the copper and zinc isozymes of SOD, inhibiting its activity against ROS. 17,18 This indicates that other oral pathogens might produce molecules that serve as defense mechanisms to disrupt the antioxidant barrier. Research into these molecules can help develop treatments that prevent antioxidant levels from becoming depleted, thereby strengthening the antioxidant barrier.…”
Section: Barriers To Antioxidantsmentioning
confidence: 99%
“…Доведено, що зміни показників пероксидного окиснення ліпідів (ПОЛ) та АОЗ у слині є більш чутливими до впливу негативних факторів, ніж аналогічні показники крові [10]. Результати численних досліджень ротової рідини пацієнтів із ЗТП показали процес активації ПОЛ, що проявлявся збільшенням вмісту малонового альдегіду відносно аналогічного показника в практично здорових осіб, виснаження неферментативної (тіоли) і ферментативної ланок АОЗ (супероксиддисмутаза, глутатіонпероксидаза та каталаза) [11][12][13][14].…”
Section: сучасні підходи до діагностики негативного впливу незнімного...unclassified